Effectors of plants pathogenic fungi and fungal like microbes: a comprehensive review on mechanisms, roles, and host interactions - Kainat,; Mujtaba, Majid; Wang, Yuting; Zhou, Boru (Frontiers in Plant Science, 2025)
Plant ecosystems face primary threats from biological invasions in combination with microbial pathogens whose main threats derive from fungal pathogens. Fungi are essential in maintaining ecological balance by decomposing wood and eliminating weakened trees, but pathogenic fungi can cause devastating effects. This review summarizes the effects of forest pathogenic fungal effectors by evaluating their types, functions, and unique characteristics, along with their impact on host immune response mechanisms. Pathogens attack plants through specific infection strategies that involve effectors to suppress host defense responses and metabolic activities. Plants falling victim to fungal effectors through their interaction with pathogens lose control of key cellular processes that allow the infection to develop. Effectors are categorized into apoplastic and cytoplasmic types, which influence plant immunity through alterations in immune responses. The infection entry process involves microorganisms that release protein effectors as structural and functional modifiers for target cells. The diversity of effectors jointly with their evolutionary processes depends on multiple factors encompassing amino acid content and foundational genomic zones together with interaction period with hosts. Effectors further manipulate phytohormone pathways such as jasmonic acid, ethylene, and salicylic acid to suppress immunity, promote pathogen survival, and establish parasitic compatibility. However, fungal effectors are central to pathogenesis, as they critically redefine plant-pathogen interactions by targeting host defense mechanism, enabling colonization, and driving diseases development. The review evaluates fungal effectors as dual agents which disrupt plant immunity while serving as research tools to study host biology. Exploring effector-mediated mechanisms helps researchers better understand fungal pathogenicity characteristics alongside plant host defense mechanisms. Future inquiries should examine pathway plasticity in effectors across taxonomic domains to better understand fungal pathogenesis in forest ecosystems worldwide.